Macedonia’s Interests in Thrace and Conflicts with Athens - Sabine Müller (Karanos)
From the late sixth century BC on, close connections between the political actors of Thrace, Hellespontine Phrygia, Persia, Athens, and, during their times of Greek supremacy, Sparta and Thebes are attested. When Macedonia advanced to the Hellespontine sphere, the basic understanding was ultimately disturbed. Aiming at controlling both sides of the straits, Philip could take the Phrygian satraps at the climax of their influence as an example and pursue a mirror-image policy. This paper explores the ways Philip’s connection with Artabazos may have provided him with insights into the political networks and structures in the area. It also considers the history of family ties between the Argeads and the family of Artabazos